Representing Periodic Motion: A Social Semiotics Analysis ofMultimodal Texts in A University Physics Chapter - Asep Ipan Wirayuda; Rizal Adimayuda (IPI Garut Press, 2026)
Physics is one of the most demanding content areas for readers because meaning is distributed across words, algebraic symbols, diagrams, and graphs at once. Although social semiotics has been proposed as a framework for understanding how texts differ across disciplines, few studies have applied it in fine detail to an advanced science topic in which several representational modes are woven together within a single explanatory sequence, such as periodic motion. This study aims to describe how a university physics chapter on periodic motion represents its content across semiotic modes and how it positions readers in relation to the discipline. Using a qualitative textual analysis guided by Wilson’s (2011) social semiotics framework, the study examines the ideational and interpersonal functions of the verbal, numeric-symbolic, diagrammatic, and graphical modes used in the chapter “Periodic Motion” from an introductory university physics textbook. The analysis shows that periodic motion is represented through four interdependent modes, each affording a kind of meaning the others cannot supply, while the impersonal, procedure-oriented prose positions the reader as an observer of stable physical relationships rather than as an interpreter constructing personal meaning. These findings extend Wilson’s framework by showing that, within a single scientific topic, multiple privileged modes are interdependent rather than merely co-occurring, with implications for how content area teachers might make these multimodal affordances explicit to students.